Monooxygenase-mediated cascade oxidation of fatty acids for the production of biopolymer building blocks - Sudheer, Pammidimarri D.V.N.; Chauhan, Sushma; Jeon, Wooyoung; Ahn, Jung Oh; Choi, Kwon Young (Biomass Conversion and Biorefinery, 2023)
This paper reviews the recent advances in the production of industrially valuable biopolymer building blocks, such as ω-hydroxy fatty acids, ω-amino fatty acids, diamines, and dicarboxylic acids, using monooxygenase enzymes of cytochrome P450 monooxygenase (CYP) or Baeyer–Villiger monooxygenase (BVMO). In particular, we highlight the use of CYP and BVMO in the oxidation of fatty acids derived from vegetable oils. Dodecanoic acid (lauric acid), (9Z)-octadec-9-enoic acid (oleic acid), (9Z,12Z)-octadeca-9,12-dienoic acid (linoleic acid), and 12-hydroxy-9-cis-octadecenoic acid (ricinoleic acid) are the most abundant saturated or monounsaturated fatty acids found in vegetable oils, such as coconut, palm, sunflower, and caster oils, respectively. The introduction of hydroxyl functional groups by CYP enzymes and ester structures by BVMO enzymes increases the hydrophilicity of the fatty acid. The subsequent conversion into other meaningful functional groups, such as keto, amino, and acidic groups, can increase the potential of the fatty acid to serve as biopolymer building blocks. Thus, the monooxygenase enzyme reaction has a relatively high potential and can contribute to the production of various high value-added and platform biochemicals, including biopolymers, biolubricants, and biosurfactants. In this review article, we emphasize the versatility of the CYP and BVMO enzymes and present several examples of their biochemical applications.
Keywords: Baeyer-Villiger monooxygenases; Biopolymer monomer; Building blockes; Cytochrome p450 monooxygenase, baeye–villige monooxygenase; Cytochrome P450 monooxygenases; Dicarboxylic acid; Dodecanoic acid; Hydroxy fatty acids; Monooxygenase enzymes; Monooxygenases; Biopolymer monomer; Cytochrome P450 monooxygenase, Baeyer–Villiger monooxygenase; Fatty acid; Vegetable oils